1989
DOI: 10.1017/s0022112089002788
|View full text |Cite
|
Sign up to set email alerts
|

Velocity-derivative skewness and two-time velocity correlations of isotropic turbulence as predicted by the LET theory

Abstract: The local-energy-transfer (LET) theory was used to calculate freely decaying turbulence for arbitrary initial conditions over a range of microscale-based Reynolds numbers 0.5 [les ] Rλ(tf) [les ] 1009, where tf is the final time of computation. The predicted skewness factor S(Rλ) agreed closely with the results of numerical simulations at low-to-moderate Reynolds numbers and followed the same general trend at larger values of Rλ. It was also found that, for Rλ(tf) [les ] 5, the LET calculation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Note, however, that the inertial eddy-turnover time has been observed in Ref. 11 as the dominant time scale.…”
Section: Introductionmentioning
confidence: 82%
“…Note, however, that the inertial eddy-turnover time has been observed in Ref. 11 as the dominant time scale.…”
Section: Introductionmentioning
confidence: 82%
“…Notable ones are those of Nakano [19], and the Local Energy Transfer (LET) theory of McComb [9,[20][21][22][23][24][25][26][27][28][29][30]; the latter being the only purely Eulerian theory which is compatible with the Kolmogorov inertial range. Convinced of the perceived intrinsic failings of the DIA based on an Eulerian framework, Kraichnan reformulated fluid dynamics to use Lagrangian variables and produced the Lagrangian-DIA [31].…”
Section: Example: the Direct Interaction Approximationmentioning
confidence: 99%
“…McComb et al [9] studied numerical solutions to the DIA and local energy transfer (LET) theories and, in contrast to Kraichnan's asymptotic prediction for the DIA, found that while neither the 'sweeping' time scale nor the inertial eddy-turnover time scale were completely effective in collapsing the modal time-correlation data, the inertial scaling became more dominant for both theories as R λ was increased. Finally, Gotoh et al [3] studied the modal time correlation using both DNS and DIA at R λ ∼ 35 and found that the sweeping time scale gave a poor collapse of the correlation data from the DIA relative to the data from the DNS.…”
Section: Jot 5 (2004) 035mentioning
confidence: 99%